Understanding the Ediacaran assemblages of Avalonia: a palaeoenvironmental, taphonomic and ontogenetic study - Liu, A; Alexander Liu (2011)
The Ediacaran Period, stretching from 635–542 million years ago, is one of the most dynamic intervals in the history of life. It witnessed the rapid transition from a microbially-dominated world, which had existed undisturbed for almost three billion years, to a Phanerozoic biosphere that is greatly modified by the interactions between macro-organisms and Earth surface systems. Ediacaran successions worldwide contain enigmatic assemblages of fossilised soft-bodied organisms. Determining the biological affinities of these fossils represents one of the major challenges in modern palaeontology. This thesis addresses some of the fundamental questions surrounding the Ediacara biota of the Avalon region from taphonomic, ontogenetic and palaeoenvironmental perspectives. Up-to-date stratigraphic ranges are produced for Avalonian macro-organisms, documenting spatial and temporal trends in their occurrence. New fossil assemblages are described, which include populations of juvenile rangeomorphs, and one of the earliest examples of community succession in the fossil record. The previously unexplained fossil Ivesheadia Boynton and Ford 1996 is re-described as a taphomorph, preserving the remains of Ediacaran macro-organisms that had died and undergone microbial decay on the seafloor prior to burial. This hypothesis implies considerable time-averaging of Avalonian palaeocommunities, and consequently suggests that the preserved fossil assemblages do not represent census populations of living organisms at the time of burial. Microbial decay is experimentally demonstrated to replicate aspects of Ivesheadia-type morphology, supporting the arguments presented herein for the preservation of microbially-induced taphomorphs during the Ediacaran. Finally, the discovery of the oldest evidence for metazoan locomotion, from 565Ma horizons at Mistaken Point in Newfoundland, suggests that motile macro-organisms were present amongst the Ediacara biota, ~20Myrs before the Cambrian boundary. This portrayal of Ediacaran palaeobiology views the deep-marine Avalonian ecosystems as diverse assemblages of both macro- and micro-organisms. Such palaeoenvironments preserve rare evidence of organisms capable of locomotion, and are likely to have included metazoans.